Lay your body down : a novel - Clarke, Amy Suiter (William Morrow, 2023)
"In Amy Suiter Clarke's brilliant sophomore thriller, a young woman returns to her rural Minnesota hometown for the funeral of her ex boyfriend-her first love-who died suspiciously, only to confront the ways a radical pastor's warped evangelical beliefs have poisoned the whole town"--